Gambaran Sanitasi Lingkungan Perumahan Y di Kabupaten Banyuwangi - Nur Aulia Rahmah (VISIKES: Jurnal Kesehatan Masyarakat, 2018)
Housing does not only function as a shelter. A good housing is housing that pays attention to all aspects such as comfort, safety and feasibility. In addition, a good home is a house that meets all the technical and health requirements. This is what then encourages to make observations on one housing in Banyuwangi. This study aims to describe or know the picture of environmental sanitation Y housing in Banyuwangi Regency. This research is included in the type of descriptive observational research with the number of samples are 10 houses. Assessment is done on two major components namely the general condition of housing and housing conditions. The general conditions of housing include waste management, distance to landfill, road access, green space, educational facilities, health, economy and security. While the condition of the house can be assessed from variable windows, ceilings, walls, sinks, storage and physical quality of clean water, mosquito larvae, ventilation in the kitchen and waste sorting. The overall scoring result of all assessment components on 10 homes is summed and divided by the maximum value. The result found that Y housing in Banyuwangi Regency included in the category enough.